From thinking to acting: Occupational self-analysis tools for use with people with intellectual disability. A pilot study - Fernandez-Solano, Ana Judit; Del Baño-Aledo, María Elena; Rodríguez-Bailón, María (Wiley, 2019)
Background. Occupational self-analysis programs have been developed in order to promote health, mainly in older adults. However, no published studies have been identified yet for people with intellectual disability. The aim of this study was to examine the effectiveness of an occupational self-analysis program in people with intellectual disability focusing on the areas of subjective health perception and participation. Methods. This study explored the benefits of the “Occupational Self-Analysis Program” in people with intellectual disability. The intervention group comprised 12 participants and the control group was composed of 13 participants. Outcomes were measured using the SF-36 Health Survey and the Role Checklist. The contents of participants’ journals and a focus group discussion were also analysed. Results. Compared to the control group, the intervention group showed statistically significant improvements in role limitations due to physical health, role limitations due to emotional problems, social functioning, and the cumulative scores of the mental component in SF-36 Health Survey. The qualitative analysis revealed that participants in the intervention group increased their participation in activities of daily living, leisure, employment seeking and acquisition, and social participation. These participants also became more aware of issues that lead to a greater engagement in meaningful occupations. Conclusion. This program allowed participants to engage in meaningful activities with other people and to increase their perceived health status by raising awareness of the strengths and difficulties of participation.
Keywords: Reahabilitación profesional; Discapacidad; Terapia ocupacional; Intellectual disability; Health promotion; Occupational therapy; Roles; Awareness